A national survey of the debonding protocols used by orthodontists in New Zealand - Wu TianYou; Farella Mauro; Guan Simon; Cannon Richard D.; Mei Li (Australasian Orthodontic Journal)
To investigate the debonding protocols used by orthodontists in New Zealand.